2002
DOI: 10.4049/jimmunol.168.11.5483
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses in 4-1BB (CD137)-Deficient Mice

Abstract: The 4-1BB (a TNFR superfamily member) is an inducible costimulatory molecule that can exert regulatory effects on T cells independently of CD28 stimulation. The in vitro expression of 4-1BB (CD137) is induced following activation of T cells with various stimuli, including anti-TCR mAbs, lectins, and a combination of PMA and ionomycin. To delineate further the physiological role of 4-1BB in immunity, mice deficient in this receptor were generated. These mutant mice developed normally, and were viable and fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
205
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(225 citation statements)
references
References 29 publications
(22 reference statements)
17
205
3
Order By: Relevance
“…Although the increased NFATc1 expression by r4-1BBL does not fit with this possibility (Fig. 5C), a similar discrepancy has been reported for the role of 4-1BB in T cell proliferation: 4-1BB -/-T cells show an increased proliferative response compared with 4-1BB +/+ T cells, despite the costimulatory effect of 4-1BBL on the proliferation of 4-1BB +/+ T cells [29,30]. The exact signaling pathways through 4-1BB and 4-1BBL warrant further clarification.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Although the increased NFATc1 expression by r4-1BBL does not fit with this possibility (Fig. 5C), a similar discrepancy has been reported for the role of 4-1BB in T cell proliferation: 4-1BB -/-T cells show an increased proliferative response compared with 4-1BB +/+ T cells, despite the costimulatory effect of 4-1BBL on the proliferation of 4-1BB +/+ T cells [29,30]. The exact signaling pathways through 4-1BB and 4-1BBL warrant further clarification.…”
Section: Discussionmentioning
confidence: 48%
“…The quite mild phenotype of 4-1BB -/-mice despite the reduced osteoclastogenic ability ex vivo may be attributed to increased myeloid cells in these mice [29] or may implicate redundancy of the 4-1BBL/4-1BB axis in normal bone homeostasis. However, 4-1BBL and 4-1BB may have an additional role in inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of 4-1BB À/À and 4-1BBL À/À knockout mice 38,39 has allowed a number of investigations into the necessity of 4-1BB:4-1BBL in immune responses. Kwon et al 39 showed that T cells from 4-1BB À/À mice had enhanced proliferation in response to mitogens, or a-CD3.…”
Section: Role Of 4-1bb:4-1bbl In Primary Immune Responsesmentioning
confidence: 99%
“…Kwon et al 39 showed that T cells from 4-1BB À/À mice had enhanced proliferation in response to mitogens, or a-CD3. However, the T-cell immune responses of 4-1BB À/À mice, as measured by cytokine production and CD8 þ Tcell cytotoxic T lymphocyte (CTL) activity, were diminished.…”
Section: Role Of 4-1bb:4-1bbl In Primary Immune Responsesmentioning
confidence: 99%